Evaluation of vitamin D3 among overweight and obese school students in Samarra city - Shafaq Abbas Muhammad Al-Samarrai; Abdul Monaim Hamad Majeed Al-Samarrai (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
current research included evaluating the level of vitamin D3 in overweight and obese school students. The research included collecting 90 blood samples, between the ages of (12-18) years, 30 blood samples were from overweight people (G1), and 30 blood samples were from people with obesity. Obesity (G2) and 30 blood samples from healthy people (control group). The samples were collected from school students in the city of Samarra, for the period from 11/12/2022 - 12/20/2022.The research included estimating the level of vitamin D3, in the blood serum of the samples under study. And Know the prevalence of Vitamin D3.The results obtained from the current study:Prevalence Study: The results showed that vitamin D3 deficiency was 100% in all study groups. As for the severity of the deficiency, it was found that the prevalence of vitamin D3 deficiency within the range (20-30)ng/ml was 40% and the range (10-20) was 60%. As for (5-10) ng/ml, it was 0% for the healthy group. As for the group G1 (overweight), the results showed that the prevalence of vitamin D3 deficiency within the range (20-30) ng /ml was 23.3%, and the range (10-20) ng /ml was 50%, while (5-10) ng/ml it was 27%, while the percentage of The prevalence of vitamin D3 deficiency for group G2 (obesity) within the range (20-30) was 10%, and the range (10-20) ng /ml was 53%, while (5-10) ng/ml it was 36%.Biochemical study : The result showed a significant decrease in Vit D3 in blood serum G1,G2 groups Compered with control groups .